The Comparative Analysis Of Multi-Criteria Decision-Making Methods (MCDM) In Priorities Of Industrial Location Development - Agusta Praba Ristadi Pinem; Aria Hendrawan; Nur Wakhidah (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2024)
The process of prioritizing the development of an industrial area's site is a matter that necessitates a mature approach. The establishment of an industrial region has significant social implications for the surrounding locality. However, it is also necessary to take into account the availability of variables that facilitate the functioning of such an industrial zone. The goal of the study